Fertilización con N, P y K en Eucalyptus grandis W. Hill ex Maiden evaluado a los nueve meses en Misiones = Fertilization with N, P y K in Eucalyptus grandis W. Hill ex Maiden evaluated at nine months in Misiones. - Von Wallis, Alejandra (2019)
To evaluate growth response to the application of nitrogen (N), phosphorus (P) and potassium (K) in the establishment of plantations of E. grandis on growth, a fertilization assay was installed. The 27 treatments, which arise from the combination of three doses of N, P and K in each case, have three repetitions. At 9 months from planting, the total plant heights were measured, from which statistical analysis result, when the combination of all the nutrients is evaluated, there are significant differences in the mean height (2.20 m) of the plants that were fertilized with 90-0-100 g / plant of NPK. When analyzing the effect of nutrients individually, there was no effect of N on the mean height of the plants, while both P and K have significantly influenced on the initial growth of fertilized E grandis.